Statistical quality control on the Noritake Porcelain Manufacturing Process - Cabrera, Rashell; De Leon, Marikris; Villa, Paulo (Quezon City College of Engineering, University of the Philippines Diliman, 2006)
A statistical process control study was conducted on Noritake Porcelana. After initial data gathering and documentation, problem analyses lead to the decision to focus on operations revolving around the glostware inspection. Comparison of recovery levels revealed that ivory class dinnerware produced by forming through outside jiggering were most problematic. A FMECA analysis conducted narrowed down priority problem areas and confirmed them to be part of the glostware block, with glazing misapplication earning an RPN of 72, followed by glaze contamination with an RPN of 70. Defect yield analyses showed that pittings topped the defect list for data from late July to mid-September. Control charts were constructed (p charts) for pittings defects and the process of producing 96620 was discovered to be in control. However, capability analyses revealed that the process is incapable of satisfying the 2% target desired by management. DOE on improving the process of making 96620 is recommended to prevent further loss. DOE strategies recommended include investigating the correlation of pittings with other defect types for identifying common causes. Kiln settings could also be the focus of DOE since they are identified potential causes of pittings.
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial quality control.
Keywords: Nippon Toki Kabushiki Kaisha; Porcelain; Quality control